Eucommia ulmoides bark extract reduces blood pressure and inflammation by regulating the gut microbiota and enriching the Parabacteroides strain in high-salt diet and N(omega)-nitro-L-arginine methyl ester induced mice - Yan, Dong; Si, Wenhao; Zhou, Xiaoyue; Yang, Mengjie; Chen, Yuanhang; Chang, Yahan; Lu, Yidan; Liu, Jieyu; Wang, Kaiyue; Yan, Moyu; Liu, Feng; Li, Min; et al. (Frontiers in Microbiology, 2022)
Hypertension is a major threat to human health. Eucommia ulmoides Oliv. (EU) is a small tree and EU extract is widely used to improve hypertension in East Asia. However, its major constituents have poor absorption and stay in the gut for a long time. The role of the gut microbiota in the anti-hypertensive effects of EU is unclear. Here, we examined the anti-hypertensive effects of EU in high-salt diet and N(omega)-nitro-L-arginine methyl ester (L-NAME) induced mice. After receiving EU for 6 weeks, the blood pressure was significantly reduced and the kidney injury was improved. Additionally, EU restored the levels of inflammatory cytokines, such as serum interleukin (IL)-6 and IL-17A, and renal IL-17A. The diversity and composition of the gut microbiota were influenced by administration of EU; 40 significantly upregulated and 107 significantly downregulated amplicon sequence variants (ASVs) were identified after administration of EU. ASV403 (Parabacteroides) was selected as a potential anti-hypertensive ASV. Its closest strain XGB65 was isolated. Furthermore, animal studies confirmed that Parabacteroides strain XGB65 exerted anti-hypertensive effects, possibly by reducing levels of inflammatory cytokines, such as renal IL-17A. Our study is the first to report that EU reduces blood pressure by regulating the gut microbiota, and it enriches the Parabacteroides strain, which exerts anti-hypertensive effects. These findings provide directions for developing novel anti-hypertensive treatments by combining probiotics and prebiotics.